2021
DOI: 10.1038/s41598-021-93894-2
|View full text |Cite
|
Sign up to set email alerts
|

Early life neonicotinoid exposure results in proximal benefits and ultimate carryover effects

Abstract: Neonicotinoids are insecticides widely used as seed treatments that appear to have multiple negative effects on birds at a diversity of biological scales. Adult birds exposed to a low dose of imidacloprid, one of the most commonly used neonicotinoids, presented reduced fat stores, delayed migration and potentially altered orientation. However, little is known on the effect of imidacloprid on birds growth rate despite studies that have documented disruptive effects of low imidacloprid doses on thyroid gland com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 64 publications
0
1
0
Order By: Relevance
“…Several studies have demonstrated that contaminants can alter the functioning of the HPT axis and the metabolism of vertebrates (e.g., Braham & Neal, 1974), but most of these studies have focused on polychlorinated biphenyls (French et al, 2001; Smits et al, 2002; Tori & Mayer, 1981; Verreault et al, 2007; Voltura & French, 2000), organochlorine pesticides (Blévin et al, 2017), polybrominated diphenyl ethers (Allen et al, 2016; Lema Sean et al, 2008), per‐ and polyfluoroalkyl compounds (Ask et al, 2021; Blévin et al, 2017; Sebastiano et al, 2021), and neonicotinoids (Zgirski et al, 2021). The potential impact of endocrine disruptors on metabolism remains neglected, especially regarding contaminants of emerging interest such as azoles.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have demonstrated that contaminants can alter the functioning of the HPT axis and the metabolism of vertebrates (e.g., Braham & Neal, 1974), but most of these studies have focused on polychlorinated biphenyls (French et al, 2001; Smits et al, 2002; Tori & Mayer, 1981; Verreault et al, 2007; Voltura & French, 2000), organochlorine pesticides (Blévin et al, 2017), polybrominated diphenyl ethers (Allen et al, 2016; Lema Sean et al, 2008), per‐ and polyfluoroalkyl compounds (Ask et al, 2021; Blévin et al, 2017; Sebastiano et al, 2021), and neonicotinoids (Zgirski et al, 2021). The potential impact of endocrine disruptors on metabolism remains neglected, especially regarding contaminants of emerging interest such as azoles.…”
Section: Introductionmentioning
confidence: 99%